2019
DOI: 10.21475/ajcs.19.13.10.p1316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organomineral fertilizers formulated with biosolids and filter cake on common bean yield crop (Phaseolus vulgaris L.)

Abstract: The objective of this research was to evaluate the efficiency of different sources of residues in the composition of organomineral fertilizers on common bean yield. The experiment was carried out in a greenhouse at the Federal University of Uberlândia. A randomized complete block design was used in the 2 x 4 + 2 factorial scheme corresponding to two organic sources (biosolids and filter cake) and four doses of pelletized organomineral fertilizer (50, 75, 100 and 125% of the recommendation for common bean, plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
3
7
0
1
Order By: Relevance
“…It was also found that the control treatment of the 0.0 kg ha -1 of the organomineral produced 50% fewer pods, an average of 5.0 pods per plant. In agreement with the result of this experiment, Silva et al (2019), when testing the e ciency of organomineral lter cake in the grain yield of bean, achieved increasing values up to the dose of 100% of the biofertilizer application of fertilizers average of 6,7 pods, and with the dose of 125% an average of 7,8 pods per plant.…”
Section: Agronomic Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…It was also found that the control treatment of the 0.0 kg ha -1 of the organomineral produced 50% fewer pods, an average of 5.0 pods per plant. In agreement with the result of this experiment, Silva et al (2019), when testing the e ciency of organomineral lter cake in the grain yield of bean, achieved increasing values up to the dose of 100% of the biofertilizer application of fertilizers average of 6,7 pods, and with the dose of 125% an average of 7,8 pods per plant.…”
Section: Agronomic Analysissupporting
confidence: 89%
“…According to data from Conab (2021), grain yield in the rainy season of 2019/2020 in Brazil was 1.209 kg ha -1 , while in autumn/winter season presented an average yield of 1.481 kg ha -1 , both lower than the highest productivity obtained in the present study -2.666 kg ha -1 . In this way it can be concluded this superiority for the organomineral fertilizer concerning the chemical fertilizer, corroborating the research results to Gurgel et al (2015), Silva et al (2019) and Frazão et al (2019), can be attributed to the adequate supply and slow availability of nutrients to plants. 4…”
Section: Agronomic Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, Saikia et al [133] reported the positive effect of the application of Rhizobium, Azotobacter and Azospirillum on organic fertilizers through the improvement of soil microbial and enzymatic activities. Da Silva et al [134] reported that the application of organomineral fertilizer (from biosolids) significantly increased yield when combined with 50% recommended dose of inorganic N, compared to control-crop treatments comprising 100% rates of organomineral, or inorganic fertilizers. Musse et al [135] also highlighted that greater pod yield was obtained by bioslurry amendments under limited N inputs.…”
Section: Fertilizationmentioning
confidence: 99%
“…Demonstrando similaridade com os resultados, Silva et al (2019) analisando em conjunto as variáveis relacionadas à produção da cultura do feijão (número de vagens, número de grãos, número de peso de mil grãos) constaram a melhor eficiência no uso de fertilizante organomineral à base de biossólidos, verificando-se que mesmo não apresentando diferenças estatísticas esses fatores foram superiores ao fertilizante mineral.…”
Section: Estádio % ----------------------Arenosa ---------------------unclassified